2001
DOI: 10.1093/emboj/20.23.6583
|View full text |Cite
|
Sign up to set email alerts
|

V-shaped structure of glutamyl-tRNA reductase, the first enzyme of tRNA-dependent tetrapyrrole biosynthesis

Abstract: contributed equally to this work Processes vital to life such as respiration and photosynthesis critically depend on the availability of tetrapyrroles including hemes and chlorophylls. tRNA-dependent catalysis generally is associated with protein biosynthesis. An exception is the reduction of glutamyl-tRNA to glutamate-1-semialdehyde by the enzyme glutamyl-tRNA reductase. This reaction is the indispensable initiating step of tetrapyrrole biosynthesis in plants and most prokaryotes. The crystal structure of glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
134
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(140 citation statements)
references
References 36 publications
(42 reference statements)
6
134
0
Order By: Relevance
“…However they do not rule out the possibility that a very rapid GSA-AM reaction in the coupled assay might also result in the protection of GSA. Nevertheless, these findings are in clear agreement with the postulated substrate channeling pathway as indicated by x-ray crystallography and by modeling experiments (5) in which the intermediate aldehyde is prevented from exposure to the aqueous environment.…”
Section: E Coli Glutr and Gsa-am Form A Complex In Cell-free Extractsupporting
confidence: 88%
See 3 more Smart Citations
“…However they do not rule out the possibility that a very rapid GSA-AM reaction in the coupled assay might also result in the protection of GSA. Nevertheless, these findings are in clear agreement with the postulated substrate channeling pathway as indicated by x-ray crystallography and by modeling experiments (5) in which the intermediate aldehyde is prevented from exposure to the aqueous environment.…”
Section: E Coli Glutr and Gsa-am Form A Complex In Cell-free Extractsupporting
confidence: 88%
“…The modeled E. coli structures were generated using the program BRAGI (19). The model complex was created by placing GSA-AM in the open space delimited by GluTR and docking them along their 2-fold symmetry axes as described previously (5). The image was generated by using PyMOL (20).…”
Section: Analysis Of Glutr⅐gsa-am Interaction By Gel Filtration Accormentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that some enzymes for chlorophyll biosynthesis are associated with other proteins and that this fe ature is important for the enzymatic activities. Glutamyl-tRNA reductase, which is involved in 5-amonolevulinic acid syntheses, has been suggested to form complexes with glutamate-1-semialdehyde-1, 2-mutase, an enzyme required for the subsequent step (Moser et al 2001). It is thought that this structure promotes the efficient synthesis of 5-amonolebulinic acids.…”
Section: Isolation Of Cao From Prochlorothrix Hollandicamentioning
confidence: 99%